Sifat Fisikokimia Pati Sorghum Varietas Merah dan Putih Termodifikasi Heat Moisture Treatment (HMT) untuk Produk Bihun Berkualitas - Kristinah Haryani (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Utilization of sorghum as food, especially as an ingredient of bihon noodles, is still very limited, even though this plant is very potential to be developed in Indonesia. This study was conducted to produce sorghum starch as an ingredient of bihon. In this researcha modification of starch was conducted by applyingheat moisture treatment (HMT) method that is able to convert starch type A to type B and even C, i.e. by heating starch with a limited water content at a temperature above the temperature of gelatinization until an arrangement of crystalinity conformation occured without gelatinization. The HMT process was carried out on the water content of 18%, 21%, 24%, 27% and 30%,at temperature of 80, 90, 100, 110 and 120 centigrade, and interval time of 4, 8, 12, 16 and 20 hour respectively. It was found that a relatively good condition at the HMT process with moisture content of 21%, temperature of 100 centigrade and heating time of 12 hour obtainning solubility of 1.67%, flower power of 4,16g/ gand resembles rice starch, in doing so it can be used as a substitute for rice starch in the making of bihon noodles.